Prezentacja dynamiki stężenia fosforu całkowitego w jeziorach reperowych w Polsce w latach 2000-2008 za pomocą sygnatur animowanych - Cybulski, Paweł (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2014)
The article focuses on how cartographic visualization of physical and geographical phenomena which were the results of the “Report on the state of the environment in Poland 2008” relates to the changes of concentration of total phosphorus in the benchmark lakes in the years 2000-2008. Environmental assessment based on the size and the dynamics of the concentration of the biogenic elements. Presentation of the data that are time-variable must also be designed in a way to reveal the nature of these changes and allow the user to understand them. Questionnaire surveys were conducted to assess the effectiveness and the appropriateness of the use of the animation in the cartographic presentation of the point phenomena that refers to changes in natural environment.
Keywords: cartographic animation; phosphorus concentration; benchmark lakes; rotating signature